Optimizing the utilization of biochar from waste: an energy–water–food nexus assessment approach considering water treatment and soil application scenarios - Obar, Farah; Alherbawi, Mohammad; Mckay, Gordon; Al-Ansari, Tareq (Frontiers in Environmental Science, 2023)
Introduction: As a result of the rapid increase in population and depletion of natural resources, particularly energy and water, approximately 200 million people are expected to face hunger by 2030. Going forward, the sustainability of energy, water, and food (EWF) resources can be enhanced by considering a nexus approach, which supports effective resource management by identifying synergies and trade-offs. Furthermore, the regeneration of biomass into value-added products, such as biochar (BC), can reduce cross-sectoral environmental impacts and support the EWF nexus. Methodology: This research investigates the optimum options for utilizing BC within the context of the EWF nexus for both wastewater treatment and soil applications whilst considering the optimal blending ratio of various biomass (camel manure, date pits, sewage sludge, and coffee waste) for both single-end use and multi-end use stages to fulfill various objectives within defined scenarios based on maximum savings in energy, water, cost, and emissions. Results and discussion: The single-end use stage considered using BC for wastewater treatment (WWT) and as a soil amendment (SA) individually, and 18 optimal solutions were collected for this stage. The optimization of the multi-end use stage resulted in 70 optimal solutions, where BC was applied for both WWT and SA. The solutions that leaned toward SA application suggested that BC should consist of 97%–99% of date pits with relatively smaller proportions of the other biomass. On the other hand, the other solutions that leaned toward the WWT pathway suggested that the optimum biomass mix should consist of relatively equal proportions of camel manure, sewage sludge, and coffee waste of 29%—33% and smaller amounts of date pits of approximately 2%–5%.